(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Time spent reading with children is one of the most impactful activities a parent or guardian can be doing. Professionals in the field of education are in the position to guide guardians towards creating a literacy-rich home environment. By doing so, educators are assisting guardians in setting their child up for the most success in life. Educators can host parent/guardian nights, develop classroom libraries, and use additional community resources to support parents or guardians in developing a literacy rich home environment. By building this bridge for parents and guardians, educators are able to ensure all students reach their greatest potential. Reading to children in the home environment can impact students’ chances of becoming successful in more ways than one.